Implementasi Sistem Pakar Diagnosa Kerusakan Hardware dan Software Laptop dengan Metode Forward Chaining Berbasis Website - Muhamad Akbar; Yolen Perdana Sari (CV. Multi Kreasi Media, 2024)
Laptops are now an important need in various fields such as business, education, communication and even entertainment. However, damage to laptop devices cannot be avoided. An expert system that uses the Forward Chaining approach to diagnose software and hardware problems on laptops is one solution that can be done. The method used in this research is qualitative by collecting data through several methods, namely observation and literature study. The data contained in this expert system consists of laptop symptoms and damage obtained from the author's personal experience, forums and communities, as well as from various other sources of information such as journals, books and the internet. The system development method in this research is the forward chaining method, which focuses on building information from the bottom up. This process begins by matching current facts with predetermined rules and then generating new information based on the logic contained in those rules. The results obtained from testing in this study show that 91% of users consider this application useful for diagnosing damage to laptops.